2022
DOI: 10.1111/bjh.18323
|View full text |Cite
|
Sign up to set email alerts
|

Asciminib for chronic myeloid leukaemia: Next questions

Abstract: The therapeutic landscape of chronic myeloid leukaemia (CML) has dramatically shifted in the past two decades, 1 transforming the disease from a primary indication for an allogeneic stem cell transplant to essentially a chronic illness. The altered paradigm is solely due to the development of tyrosine kinase inhibitors (TKIs) that target the diseasedefining BCR-ABL1 fusion 2 with the first foray into targeted therapy being imatinib, the first-generation TKI. 3 With the introduction of imatinib, and the subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
(213 reference statements)
0
6
0
Order By: Relevance
“…Based on the current evidence, we do not recommend switching from imatinib to nilotinib for a second attempt. The recommendation may differ for news inhibitors, such as asciminib, particularly if their safety profile and efficacy are confirmed in the future 27 …”
Section: Discussionmentioning
confidence: 99%
“…Based on the current evidence, we do not recommend switching from imatinib to nilotinib for a second attempt. The recommendation may differ for news inhibitors, such as asciminib, particularly if their safety profile and efficacy are confirmed in the future 27 …”
Section: Discussionmentioning
confidence: 99%
“…Asciminib was introduced after approval by the US Food and Drug Administration (FDA) into clinical practice in 2021 in CML patients after resistance and/or intolerance to two previous lines of treatment [47]. The detailed characteristics of asciminib are set out in Table I.…”
Section: New Concept Of Bcr-abl1 Tyrosine Kinase Inhibitionmentioning
confidence: 99%
“…On fusion of ABL1 to BCR, myristoylated N-terminal is lost and ABL1 kinase is activated. By allosterical binding of myristoyl site, asciminib mimics myristate and restores inhibition of BCR-ABL1 kinase activity [46,47] After binding to myristoyl pocket of ABL1 kinase domain, asciminib induces an inactive conformational change and inhibits kinase activity [45] Half-life time (T CCyR were obtained and maintained in 74% and 53% of patients, respectively. MR 4.5 was confirmed in 16% of the studied patients (10.5% in PPT vs. 19.4% in the non-PPT group).…”
Section: Bcr-abl1 Tyrosine Kinase Inhibitory Mode Of Actionmentioning
confidence: 99%
“…These unmet needs motivate the search for additional drugs to manage this subset of patients. Asciminib, the first example of an allosteric inhibitor, has been recently approved by the FDA and EMA as third-line treatment in chronic-phase CML (CP-CML) patients after resistance and/or intolerance to two previous lines of treatment [ 6 ]. Recently, a median 4-year follow-up of a phase 1a trial has been reported for 115 non-T315I mutated patients.…”
Section: Introductionmentioning
confidence: 99%